NARASI RAKYAT JELATA DALAM EPOS KANJENG KIAI SERAT BRATAYUDA - Sumiyardana, Kustri (Pusat Riset Manuskrip, Literatur, dan Tradisi Lisan, 2024)
Kanjeng Kiai Serat Bratayuda is an heirloom manuscript of the Yogyakarta Palace. The text contains the story of the battle between the Pandavas and Kauravas. Actually, this story comes from India. The story has been revised and there are several additions. One of the additions in Kanjeng Kiai Serat Bratayuda is the emergence of figures from the common people. The problem in research is the role of ordinary people's figures. Text handling begins with transliteration, translation and analysis. Based on the research results, it can be seen that commoner figures can be classified into two, namely named figures and unnamed figures. The common people are shown as a reflection of society at that time and the background to bring the story to life. In addition, commoners are shown as a joke interlude.